The Extent and Patterns of Multiple Chronic Conditions in Low-Income Children. (April 2015) - Clark, Noreen M.; Lachance, Laurie; Benedict, M. Beth; Little, Roderick; Leo, Harvey; Awad, Daniel F.; Wilkin, Margaret K.
Background and objectives . Little is known about the magnitude of multiple chronic conditions (MCC) in children. This study describes the prevalence of and patterns of comorbidities in children receiving Medicaid assistance. Methods . Diagnoses from 5 years of Medicaid claims data were reviewed and identified 128 044 children with chronic conditions. The relationship between comorbidities and significant urgent health care events was analyzed using logistic regression modeling. Results . More than 15 000 children (12%) had claims for more than 1 condition. The most frequent combination was asthma and allergic rhinitis. Significant health care events ranged from 18% to 51% in children, and the odds of having a significant event increased with each additional condition. Those with ≥4 conditions had 4.5 times the odds of a significant event compared with those with 1 condition ( P < .0001). Conclusion . MCC are prevalent in low-income children and are associated with greater risk for urgent health care use.